THE PRINCIPLE OF NON-INTERFERENCE CURTAILS ASEAN ACTION IN ADDRESSING HUMAN RIGHTS VIOLATION IN MYANMAR (Journal of International Studies, 2024)
This article described and analyzed the dilemma faced by ASEAN under its non-interference principle in managing the human rightsissues in Myanmar. The presence of that principle severely curtails ASEAN’s firm action to promote and protect human rights stronglybased on the ASEAN’s commitment written in the ASEAN Charter and the ASEAN Declaration of Human Rights (ADHR). This articleutilizes the qualitative research method supported by secondary data to provide an in-depth and comprehensive analysis. ASEAN’sprotection of human rights is reflected by its active conduct of regular discussions and engagements on human rights issues in the region, the adoption of the ADHR, and the establishment of the ASEAN Intergovernmental Commission on Human Rights (AICHR). Thehuman rights issues gained more attention in ASEAN in 1997 as the United States and European Union opposed the ASEAN decision toaccept Myanmar as a member on the grounds of the human rights violations record in Myanmar. The membership in ASEAN did notimprove the human rights record in Myanmar as ASEAN had hoped for. Myanmar embarked on other human rights violations, amongothers the Rohingya crisis (2012) and the military coup against the democratic government (2021) that sparked criticism from abroadand within ASEAN. This study concluded that the principle of noninterference has set the limit and curtailed ASEAN’s contributiontoward optimally addressing human rights violations in Myanmar. ASEAN may need in the future a new and comprehensive mechanism for addressing human rights violations. A stronger constructive engagement policy should be put in place to set a universal standard to protect human rights in the region.